VARIATIONS IN PEAK EXPIRATORY FLOW MEASUREMENTS ASSOCIATED TO AIR POLLUTION AND ALLERGIC SENSITIZATION IN CHILDREN IN SAO PAULO, BRAZIL - de M Correia-Deur, Joya Emilie (2012)
BACKGROUND: In the last 20 years, there has been an increase in the incidence of allergic respiratory diseases worldwide and exposure to air pollution has been discussed as one of the factors associated with this increase. The objective of this study was to investigate the effects of air pollution on peak expiratory flow (PEF) and FEV(1) in children with and without allergic sensitization. METHODS: Ninety-six children were followed from April to July, 2004 with spirometry measurements. They were tested for allergic sensitization (IgE, skin prick test, eosinophilia) and asked about allergic symptoms. Air pollution, temperature and relative humidity data were available. RESULTS: Decrements in PEF were observed with previous 24-h average exposure to air pollution, as well as with 3 to 10 day average exposure and were associated mainly with PM(10), NO(2) and O(3). in all three categories of allergic sensitization. Even though allergic sensitized children tended to present larger decrements in the PEF measurements they were not statistically different from the non-allergic sensitized. Decrements in FEV(1) were observed mainly with previous 24-h average exposure and 3-day moving average. CONCLUSIONS: Decrements in PEF associated with air pollution were observed in children independent from their allergic sensitization status. Their daily exposure to air pollution can be responsible for a chronic inflammatory process that might impair their lung growth and later their lung function in adulthood.